Leadership Influence on Work Performance in Health Care Professionals: A Narrative Review - Shamiksha; Ankitha (International Journal of Behavioral Sciences, 2026)
Leadership plays an important role in influencing work performance, job satisfaction, and employee engagement among healthcare professionals. The healthcare sector is demanding and complex, making effective leadership essential for maintaining workforce well-being and quality patient care. This narrative review aims to explore the influence of different leadership styles on the work performance, job satisfaction, and engagement of healthcare professionals, and to identify effective leadership approaches that enhance teamwork, productivity, and overall healthcare outcomes. 21 peer-reviewed articles published between 2010 and 2025 were retrieved from PubMed and Semantic Scholar using relevant keywords. Leadership styles examined included transformational, servant, democratic, digital, collective, caring, authoritarian, and laissez-faire leadership. The findings indicate that transformational, servant, democratic, and caring leadership styles are consistently associated with higher job satisfaction, stronger employee engagement, improved teamwork, and better work performance. Digital leadership contributes positively by improving efficiency, communication, and employee empowerment through technology. In contrast, authoritarian and laissez-faire leadership styles are linked to increased stress, reduced motivation, role ambiguity, and lower performance. The review also highlights the importance of leadership training programs in developing leadership competencies and supportive work environments. Overall, the evidence suggests that adopting positive and people-centered leadership styles can improve employee well-being, healthcare service delivery.
Keywords: Job satisfaction; employee engagement; healthcare professionals; leadership styles; leadership training; work performance